Chemical models of adenine precursors cyanamide and carbodiimide in the interstellar medium. Issue 1 (15th March 2023) - Zhang, Xia; Quan, Donghui; Li, Runxia; Esimbek, Jarken; Chen, Long-Fei; Zhao, Guoming; Zhou, Yan
ABSTRACT: Cyanamide (NH2 CN) and its isomer, carbodiimide (HNCNH), may form adenine in the interstellar medium (ISM) via a series of reactions. Therefore, they are considered key prebiotic molecules in the study of the origin of life. We used the three-phase NAUTILUS chemical code, which includes the gas, the dust surface, and the icy mantle, to investigate the formation and destruction of cyanamide and carbodiimide. We added over 200 new chemical reactions of the two isomers and related species and established a relatively complete network. We applied cold core, hot corino/core, and shock models to simulate the different physical environments, and found that the two isomers are mainly produced by the free radical reactions on grain surfaces. Our simulated results suggest that cyanamide and carbodiimide molecules come from surface chemistry at early evolutionary stages. Then they are released back to the gas phase, either by thermal process (in hot cores, hot corinos) or by shock-induced desorption (in shock regions). We speculate that it is an inefficient route to form a tautomer of adenine by starting from molecules cyanoacetylene (C3 NH), cyanamide, and carbodiimide in ISM.